Epidemiology of Hepatitis C Infection and its Public Health Implications in Puerto Rico - Pérez, Cynthia M.; Suárez, Erick; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2013)
Hepatitis C infection is the most common chronic blood-borne pathogen in the United States associated with liver cirrhosis and hepatocellular carcinoma and is the leading reason for liver transplantation. It has been estimated that hepatitis C infection may lead to a substantial health and economic burden over the next 10 to 20 years. The prevalence of hepatitis C virus (HCV) infection varies worldwide, with an estimated overall prevalence of 3%. However, the only available data of hepatitis C in the general population of Puerto Rico suggest an elevated prevalence of hepatitis C infection in the municipality of San Juan (6.3%) in comparison with estimates for the adult population residing in the United States (0.9%-3.9%). Much of the inter-region variability in the prevalence of hepatitis C can be attributable to the frequency and extent to which different risk factors have contributed to the transmission of the virus. Established risk factors for infection include injection drug use, transfusion of blood and solid organ transplantation from infected donors prior to July 1992 and blood clotting products before 1987, occupational injury, vertical transmission, sex with an HCV infected partner, and multiple sexual partners. Other potential exposures for infection that have been investigated in epidemiologic studies include history of intranasal cocaine use, sharing of contaminated equipment and personal care items, tattooing, body piercing, imprisonment, acupuncture, and use of contaminated healthcare instruments. The high incidence of AIDS in Puerto Rico and the large prevalence observed in Puerto Rican inmates and in adults residing in the municipality of San Juan indicate that HCV infection is an emerging public health concern. From a public health perspective, potential targets for intervention to decrease the spread of HCV infection, ongoing surveillance, increased clinician awareness of disease reporting systems and the epidemiology and management of hepatitis C, availability of diagnosis and treatment facilities, and recognition of the need for local resources will be of paramount importance to face this silent infection in Puerto Rico.